Modeling the influence of body mass on resistance exercise performance of non-athletes - Kulkamp W.* (2014)
© 2015 Elsevier Masson SAS.Aim: The purpose of this study was to verify the appropriateness of allometry to provide a size-independent index of resistance exercise performance of non-athletes and to compare men and women from absolute and allometric perspectives. Materials and methods: Twenty-five healthy individuals participated in the study: 11 men (22±3 years; 69.91±8.14 kg; 1.75±0.09 m) and 14 women (22±3 years; 55.92±5.94 kg; 1.65±0.09 m). They were evaluated using Bench Press and Leg Press 45° exercises. Log-linear regressions were established from natural logarithms of the values of body mass and muscle strength (weight lifted in kilograms), and regression diagnostics were performed to evaluate the suitability of the allometric model (y =ax b). Results: The results indicate that men were stronger in all exercises, even after scaling, but when the body mass effect was partitioned out allometrically, the difference of muscle strength between genders was reduced by 5% for superior limbs and 12% for inferior limbs. The problems associated with the residuals distribution observed in previous studies involving weightlifting athletes were not observed in this study, which indicates that allometry may be used with non-athletes. Thus, allometric modeling should be considered an adequate scaling method to compare the resistance exercise performance of groups when the specific training program's efficacy or different sports are taken into account. Objectifs: Matériels et méthodes: Résultats: